Sero-epidemiology of Bluetongue and Caprine arthritisencephalitis in goats of middle Indo-Gangetic plains - KUMAR, PANKAJ; RAJAK, KAUSHAL KISHORE; JEGAVEERA-PANDIAN, SANKARIAH; MAHTO, DINESH; KUMARI, RASHMI REKHA; ROY, RAMA KRISHNA; KUMAR, ABHAY (The Indian Journal of Animal Sciences, 2018)
The study was undertaken in middle of Indo-Gangetic plains of India. Bluetongue (BT) is endemic throughout the country. However, Caprine arthritis-encephalitis virus (CAE) is sporadically reported from India. The study was undertaken to evaluate the burden of these viral diseases of goat due to unavailability of systemic study in the region. Commercial ELISA kits were used for the study. BTV antibody sero-surveillance was undertaken in 504 random serum samples and Lentivirus antibody sero-surveillance for CAE in 280 random serum samples. None of the goats covered under the study had any form of clinical manifestations of these diseases. The study revealed moderate (15.64%) sero-positivity of BTV antibody and only two cases of sero-positivity of CAE. Two positive cases of CAE in Sirohi breed was brought from Rajasthan. Overall sero-positivity of BTV antibody in male was higher than female goats. The binary regression of circulating BTV antibody was significant for Sirohi and Black Bengal breeds under the study indicating breed differences.